GREEN WASHING: KECURANGAN NON-LAPORAN KEUANGAN DAN MOTIVASI KECURANGAN - Alexander, Nico; Christina, Silvy; Anggreani, Fanny (E-Jurnal Akuntansi TSM, 2026)
The environment is currently one of the most important things to protect. The government has implemented regulations for environmental preservation, especially for companies. Companies' activities in protecting the environment can be seen in their published sustainability reports. However, these reports sometimes do not reflect what the companies actually do. Most companies only provide a narrative of their activities without accompanying concrete actions. This has given rise to a new form of fraud called greenwashing. This study was conducted to obtain empirical evidence of the influence of motivation to commit fraud in the perspective of the fraud triangle, namely pressure, opportunity, and rationalization. A total of 132 non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2024 were used as research samples. Sample selection was carried out using purposive sampling. Hypothesis testing was conducted using multiple regression through the Stata application. The test results showed that pressure, measured using financial stability, and rationalization had an influence on greenwashing. This indicates that poor financial conditions of a company can increase the likelihood of greenwashing. In addition, the amount of costs incurred for environmental preservation can encourage greenwashing. The results of this study are expected to provide information for investors and regulators regarding the existence of fraud that is exploited in addition to fraud through financial reports, so that more supervision can be carried out through regulations.